Odpowiedzi

  • Użytkownik Zadane
2010-04-13T18:37:25+02:00
2*(-3)+6=-6+6=0
-5 *(-8) - 16=40-16=24
2*(-5)+3 * (-2)=-10-6=-16
8-6*(-5)=8+30=38
6-(-16):(-8)=6-2=4
5*(-2)- (-2) *6=-10+12=2
(2-6)*(-8)=-4*(-8)=-32
-5 * (-6-10)=-5*(-16)=80
-3 * (-1)-(-10)*4=-3+40=37
(-5-6):(-11)=-11:(-11)=1
24 : (-3-5)=24:(-8)=-2
(-8 + 30 ):(-7-4)=22:(-11)=-2
Najlepsza Odpowiedź!
2010-04-13T18:38:14+02:00
2*(-3)+6= 0
-5 *(-8) - 16= 24
2*(-5)+3 * (-2)=-16
8-6*(-5)= -10
6-(-16):(-8)=- 12
5*(-2)- (-2) *6=2
(2-6)*(-8)= 32
-5 * (-6-10)=80
-3 * (-1)-(-10)*4=-37
(-5-6):(-11)=1
24 : (-3-5)=-3
(-8 + 30 ):(-7-4)= - 2